2012
DOI: 10.5658/wood.2012.40.6.363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Withdrawal Strength of Wood Screws in Domestic Wood by Shear Strength with Different Growth Ring Orientation

Abstract: Shear tests parallel to the grain were conducted on domestic wood samples with different growth ring orientations. Shear strength was dependent on the angles between the direction of growth ring orientation and the applied force. The maximum shear strength showed at the intermediate growth ring orientations. Results of shear tests were also used to modify the formula which had previously been developed to predict the withdrawal strength of screw on the face of lumber. Predicted equations were fitted to the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Cha (2011) has studied on predicting the withdrawal load of wood screws in domestic wood depending on screw diameter, penetration depth and specific gravity of wood. Cha (2012) has performed research on the withdrawal strength of wood screws in domestic wood depending on the shear strength with different growth ring orientation. Oh (2013) measured the withdrawal and lateral resistance of nail joints composed of dimension lumber and OSB, which is commonly used in light-frame wood construction, and reported that withdrawal-resistance is proportional to the density of lumber.…”
Section: Introductionmentioning
confidence: 99%
“…Cha (2011) has studied on predicting the withdrawal load of wood screws in domestic wood depending on screw diameter, penetration depth and specific gravity of wood. Cha (2012) has performed research on the withdrawal strength of wood screws in domestic wood depending on the shear strength with different growth ring orientation. Oh (2013) measured the withdrawal and lateral resistance of nail joints composed of dimension lumber and OSB, which is commonly used in light-frame wood construction, and reported that withdrawal-resistance is proportional to the density of lumber.…”
Section: Introductionmentioning
confidence: 99%